UJI KANDUNGAN VITAMIN A TANAMAN WORTEL (Daucus Corata L.) DI DESA NGABAB KABUPATEN MALANG - Beta Herilla Sekti; Rakhmadani Gadis Aprilianti; Susi Wijiastini (HERBAPHARMA : Journal of Herb Farmacological, 2021)
Carrot plant (Daucus carota L.) is a type of vegetable that contains lots of vitamin A and is very much needed by the body to help regulate or metabolic processes in the body. The research design used in this study was experimental, the population and sample were carrots from Ngabab village aged 3-3.5 months, using purposive sampling technique. The results of the qualitative analysis showed that there were orange spots with an Rf value of 0.64 in the carrot extract and the beta-carotene comparison standard. The results of the quantitative analysis showed that the average level of vitamin A in carrots was 49.7% with an absorbance of 0.649. Keywords: Visible Spectrophotometry, Vitamin A, Carrot.